An ancient reservoir of volatiles in the Moon sampled by lunar meteorite Northwest Africa 10989. (1st December 2019) - Stephant, A.; Anand, M.; Ashcroft, H.O.; Zhao, X.; Hu, S.; Korotev, R.L.; Strekopytov, S.; Greenwood, R.C.; Humphreys-Williams, E.; Liu, Y.; Tang, G.; Li, Q.; et al.
Abstract: Northwest Africa (NWA) 10989 is a recently found lunar meteorite we used to elucidate the history of volatiles (H and Cl) in the Moon through analysis of its phosphates. The petrology, bulk geochemistry and mineralogy of NWA 10989 are consistent with it being a lunar meteorite with intermediate-iron bulk composition, composed of 40% of mare basaltic material and ∼60% non-mare material, but with no obvious KREEP-rich basaltic components. It is probable that the source region for this meteorite resides near a mare–highlands boundary, possibly on the farside of the Moon. Analyses of chlorine and hydrogen abundances and isotopic composition in apatite and merrillite grains from NWA 10989 indicate sampling of at least two distinct reservoirs of volatiles, one being similar to those for known mare basalts from the Apollo collections, while the other potentially represents a yet unrecognized reservoir. In situ Th-U-Pb dating of phosphates reveal two distinct age clusters with one ranging from 3.98 ± 0.04 to 4.20 ± 0.02 Ga, similar to the ages of cryptomare material, and the other ranging from 3.32 ± 0.01 to 3.96 ± 0.03 Ga, closer to the ages of mare basalts known from the Apollo collections. This lunar breccia features mixing of material, among which a basaltic D-poor volatile reservoir which doesn't appear to have been recorded by Apollo samples.